Persuasion, justification and the communication of social impact - Manuel Förster; Joël J. van der Weele (Tinbergen Institute, 2018)
We experimentally investigate strategic communication about the impact of prosocial actions, which is central to policy debates about foreign aid or the environment. In our experiment, a “sender” receives an informative but noisy signal about the impact of a charitable donation. She then sends a message to a “receiver”, upon which both subjects choose whether to donate. The sender faces a trade-off between persuading the receiver to act and justifying her own inaction. We find evidence for both motives. Increasing the visibility of the sender's actions increases the justification motive and makes senders more likely to report low impact, reducing giving among receivers. These results show the intimate links between reputation and com- munication in moral domains, and help understand the fraught nature of political discussions about social impact.
Keywords: C91; D83; D91; 330; cheap talk; image concerns; information aggregation; charitable giving; economic experiments